1989
DOI: 10.1128/mcb.9.8.3360
|View full text |Cite
|
Sign up to set email alerts
|

U1 small nuclear ribonucleoprotein particle-specific proteins interact with the first and second stem-loops of U1 RNA, with the A protein binding directly to the RNA independently of the 70K and Sm proteins.

Abstract: The Ul small nuclear ribonucleoprotein particle (Ul snRNP), a cofactor in pre-mRNA splicing, contains three proteins, termed 70K, A, and C, that are not present in the other spliceosome-associated snRNPs. We studied the binding of the A and C proteins to Ul RNA, using a Ul snRNP reconstitution system and an antibody-induced nuclease protection technique. Antibodies that reacted with the A and C proteins induced nuclease protection of the first two stem-loops of Ul RNA in reconstituted Ul snRNP. Detailed analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…The same system that was used for the in vitro assembly of Ul snRNP (30)(31)(32) and U2 snRNP (16) was used to assemble in vitro-transcribed U5 1 2 3 4 5 6 7 8 9 10 11 12 13 14 1 2 3 4 5 6 7 8 9 10 11 12 RNA (see Materials and Methods) into an RNP. The particle had a sedimentation coefficient of 9S, but since no 20S particle containing labeled U5 RNA was observed, the incubation conditions were adjusted (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same system that was used for the in vitro assembly of Ul snRNP (30)(31)(32) and U2 snRNP (16) was used to assemble in vitro-transcribed U5 1 2 3 4 5 6 7 8 9 10 11 12 13 14 1 2 3 4 5 6 7 8 9 10 11 12 RNA (see Materials and Methods) into an RNP. The particle had a sedimentation coefficient of 9S, but since no 20S particle containing labeled U5 RNA was observed, the incubation conditions were adjusted (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…(30,32), and the isolated RNA was digested with nuclease P1 Gradient centrifugation. Cesium sulfate (1.25-to 1.75-g/ cm3 step) and glycerol gradients (10 to 30% linear) were prepared and centrifuged as described previously (24,31).…”
Section: Methodsmentioning
confidence: 99%
“…HeLa cell U2 snRNP contains two unique proteins called A' and B"; neither has been shown to bind directly to U2 snRNA, although B" has an RNA recognition motif (19,20,29). Models of the Ul and U2 snRNPs have been proposed (19,20,24,26). No unique U2 snRNPs are known in S. cerevisiae.…”
mentioning
confidence: 99%
“…RNA samples were treated with proteinase K in 1% SDS and extracted with phenol and phenol/chloroform+ RNAs recovered by ethanol precipitation were fractionated through 10 or 12% polyacrylamide/urea gels and visualized by silver staining, ethidium bromide staining, or autoradiography (Fig+ 2)+ Proteins from nuclear extracts or purified snRNP particles were resolved on 10 or 12% polyacrylamide/SDS gels polymerized in the presence of very high TEMED concentration (0+07%)+ Proteins were detected by staining with Coomassie brilliant blue R-250 (and autoradiography when required) or by immunoblot with the monoclonal antibodies 4G3 (Habets et al+, 1989;Flickinger & Salz, 1994) and Y12 (Lerner et al+, 1981)+ Electroblotting was performed in 10 mM CAPS transfer buffer, pH 11, containing 10% methanol+ Immunoreactive proteins were detected using horseradish peroxidaseconjugated secondary antibodies (Bio-Rad) and the ECL reagent (Amersham)+…”
Section: Rna and Protein Analysismentioning
confidence: 99%
“…Splicing of nuclear introns occurs by a two-step pathway, conserved in eukaryotes, which takes place in a large ribonucleoprotein structure, termed the spliceosome (Sharp, 1994;Staley & Guthrie, 1998)+ The assembly of this complex requires the ordered interaction of numerous splicing factors and the five small nuclear ribonucleoproteins (snRNP) U1, U2, U5, and U4/U6+ These spliceosomal snRNPs each contain a small RNA molecule, several snRNP-specific proteins and seven common proteins (B/B9, D1, D2, D3, E, F, and G; )+ The Sm core proteins are evolutionarily conserved (Hermann et al+, 1995;Séraphin, 1995) and found in organisms as diverse as yeast, plants, fly, mouse, and man, with a molecular weight ranging from 9 to 29 kDa+ They associate with the RNA polymerase II-transcribed U1, U2, U4, and U5 snRNAs in the cytoplasm on an uridylic acid-rich region flanked by two stem-loop structures, the so-called Sm binding site (Branlant et al+, 1982)+ The formation of this Sm core RNP structure is essential for the hypermethylation of the snRNA 59 cap structure to generate the 2,2,7-trimethylguanosine (m 3 G) form (Mattaj, 1986)+ The m 3 G cap, together with the Sm proteins, also constitutes the nuclear localization signal required for the nuclear targeting of the snRNP particles (Fischer & Lührmann, 1990;Hamm et al+, 1990;Fischer et al+, 1993)+ In contrast, the U6 snRNA, which is transcribed by RNA polymerase III, possesses a monomethylguanosine cap and associates in the nucleus with the U4 RNP to form the U4/U6 functional particle+ In addition to U1 snRNA and the common Sm proteins, the human U1 snRNP particle contains three U1-specific proteins denoted 70K, A, and C+ Both proteinprotein and protein-RNA interactions are required for the association of these proteins with U1 snRNP particles+ For example, U1-70K and U1-C interact with Sm proteins during U1 snRNP assembly (Nelissen et al+, 1994), whereas U1-70K and U1-A interact, through their highly conserved RNA binding domain (RBD or RNP-CS), with stem-loops I and II of U1 snRNA, respectively (Patton et al+, 1989;Scherly et al+, 1989)+ These specific proteins are primarily responsible for fulfilling the function of U1 snRNP during the early events of spliceosome assembly, that is, the recognition of 59 splice sites on the pre-mRNA+ In mammalian nuclear extracts, this stage involves base pairing between the 59 end of U1 snRNA with conserved sequences spanning the 59 splice site (Zhuang & Weiner, 1986) and the formation of a stable U1 snRNP/pre-mRNA complex designated the early or E complex (Michaud & Reed, 1991)+ U1-C, but not U1-A, was shown to enhance the formation of E complexes (Will et al+, 1996) as well as the interaction of U1 snRNP to the 59 splice site (Heinrichs et al+, 1990;Jamison et al+, 1995)+ It is also at ...…”
Section: Introductionmentioning
confidence: 99%